Analysis of Energy Sharing Impacts in a Commercial Community: A Case of Battery Energy Storage System Deployment for Load Leveling - Li, You; Wang, Yafei; Fukuda, Hiroatsu; Gao, Weijun; Qian, Fanyue (Frontiers in Energy Research, 2022)
Energy use differences between day and night have been a key point in the efficient use of utilities. The battery energy storage system (BESS) is an attractive solution to level the grid load and has been introduced independently into many communities, although with high costs. Battery sharing presents the possibility of integrating independent energy storage systems to save money and improve energy use. Battery sharing highlights the interactions between a smart grid, smart buildings, and distributed energy storage to produce better energy management practices. In this work, we provide an analysis of battery sharing by establishing a coordinated control model for a distributed battery system. In our case study design, we selected 39 buildings with different capacities of energy storage systems as a battery-sharing community to optimize sharing schedules and the load-leveling performance. The results indicate that battery sharing could achieve a 13.2% reduction in building battery capacity compared with independent operation. We further investigate the impact of a building’s load profile patterns on the battery capacity in a battery-sharing community. It is economical to introduce a larger capacity battery system into buildings with no closing days and higher electricity consumption throughout the year. The optimal BESS capacity in commercial buildings depends on the lowest daytime power consumption. Commercial buildings with closing days have limitations regarding BESS deployment. On closing days, buildings can only use BESS by sharing. Buildings with two closing days a week lose 14.3% more energy than those with one closing day.